State-oriented maintenance strategy for deteriorating segmental lining of tunnel - Ai, Qing; Yuan, Yong (Journal of Civil Engineering and Management, 2018)
The lining of tunnel is the principal part in ensuring its usage for transportation or utilities. Maintenance during operation is the way to keep structure in the state of high performance. To consider the efficiency of maintenance within limited resources (maintenance cost), state-oriented maintenance (SOM) approach is proposed. The SOM approach takes service state of the tunnel lining as a levelled target which should be maintained by different degrees of repairing measures. The evolution of service state of tunnel lining is modelled as a non-stationary Gamma process in this investigation, as this process can characteristic the variations of degradation rates. Two cases of numerical analysis with SOM approach give their lifetime maintenance costs. Case one (MS-1) sets SOM strategy with two-levelled service state. The other case (MS-2) adopts SOM strategy with multi-levelled service state. The numerical results demonstrate that the later one would reduce maintenance cost during the whole service life of tunnel lining.